Genética e melhoramento do guando (Cajanus indicus spreng.) - Bastos de Menezes, Osvaldo (Revista Ceres, 1956)
I) An improvement program on the pigeon pea (CaJanus indicus Spreng) comprising genetical as well as cultural investigations was set out in 1941 - 1942, some results being given in this paper. II) The genetical investigations started with close inbreeding of 4 so called types differentiated by their seed coat ( black, white, chocolate and spotted white), followed almost simultaneously by reciprocal crosses between those types. III) Inheritance of some characters was studied and may be summarized as follows: a) Seed coal. There seems to be 4 different colors and which Mendelian behaviour is: black is dominant over the other three; chocolate and spotted dominate over white. Crossing chocolate and spotted, the FI is black. Black depends on the interaction of “ chocolate ” and “ spotted ”. Using Dave's factorial symbolism, the various genotypes for white would be pp rr, for chocolate RR pp, Rr PP, for spotted rr PP, rr Pp and for black PP RR, PP Rr, Pp RR or Pp Rr, The observed data closed agreed to the theoretical expe- ctations. b) Flower (standard ) color. Six different colors have been found: yellow veined with red, purple veined purple, bloodish and yellow having purple veinus with base diffu- sed purple. The bloodish color sesms to be mentioned for the first time. Based on Dave's factors P, A, CE. and iu- troducing S for bloodish culor which act in-presence of C, E, V, the crosses segregated as follows: I. yellow x veined yellow, the FI was veined yellow and the F2 segregated in accordance to the ra- tio 3:1; 2 — yellow x purple, the FI geration was purple and the F2 segregated in 3:1; 3 — purple x veined purple, the FI was veined purple and the F2 geration segregated in accordance to one factor pair hypothesis; 4 — purple x yellow having purple veins with base diffused purple, the F1 was purple and the F2 segregated on monofatorial basis; 5 — veined purple x bloodish, the F1 was bloodish and the F2 dissociated in accordance to a factor pair hypothesis; 6 — yellow x yellow having purple veins with base, diffused purple, the F1 was veined yellow with base diffu- sed purple and the segregants on the F2 generation were in accordance to the monofatorial ratio. The genotypes of the various standard colors would be. AA pp ce ee vv ss — yellow aa pp cc ee vv ss — yellow AA pp cc ee VV ss — yellow veined with red AA pp CC EE vv ss — purple AA pp CC ee vv ss - yellow veined with purple, base diffused 2 purple AA pp CC EE VV ss — purple veined AA pp CC EE VV SS — bloodish The observed data close agreed to the theoretical values and the statistical analysis dind’t show significance whatsoever. c — pod color. There seems to be 3 colors, viz, marron, green blotched and green. Marron is dominant over all the others and green blotched dominate over green. The observed segregations close fit the theoretical ratios. The genotypes would be: LL DD — marron LL dd — green blotched 11 dd — green d — pod size. Crosses between flat pods and round pods didn’t show Mendelian ratios, although Krauss has mentioned that flattened is dominant. e,f — plant height and secondary branching. Plants were grouped in tall (1,90 meter) and medium ( 1,50 meter ) at 15 months old, and crosses between them seems to indicate quantitative inheritance. Identical conclusions seems to fit the inheritance of secondary branching of 30° and 60º. It seems to exist close linkage of purple flower to black seed, and yellow veined flower to green pod. IV — As the wind is the main responsible cause in the braking of secondary branching, an experiment to decre- ase its effects was made with 6 treats, the treats being prunnings at different intervals (after irst seed harvest, 2 nd harvest, 3 rd harvest, annually prunning and branching formation half meter above the soil level and test). The observations were carried out for 2 years and the analy- sis of variance didn't show any significance, although the prunning plots were much more free of wind injury. V — In a sandy soil representative of the region where these studies were done, an experiment of fertilizers on randomized blocks with 6 reps were made and followed in 1952 and 1953. The fertilizers used were a combination of N P K Ca in different proportions. The variance showed significance only for “Year ”.